Economic development of agricultural food enterprises on an innovative basis - Chikov, I.; Чіков, I.; Radko, V.; Радько, В.; Marshalok, M.; Маршалок, М.; Tepliuk, M.; Теплюк, М.; Petrenko, O.; Петренко, О.; Sharko, I.; Шарко, І.; et al. (Товариство з обмеженою відповідальністю «ФІНТЕХАЛЬЯНС», 2022)
Abstract. The agri-food sector has been and remains the basis of Ukraine’s economy. Today, in the face of industrial decline and the all-encompassing process of deindustrialization of the economy, agri-food enterprises remain stable market players. Despite obstacles to development, agro-holdings have long dominated the agri-food market, accumulating significant land and financial resources. The largest companies are Kernel, UkrLandFarming, MHP, Agroposperis and Astarta-Kyiv, whose land banks exceed 200,000 hectares. These companies employ almost 75,000 workers. Agricultural holdings invest in their own development. One of the priority areas is innovative development. It is innovation that provides stability and a future for companies. The largest innovation fund is owned by Kernel, which spent $ 2.7 million, MHP — 2.5, AP Group — 2, Astarta-Kyiv, Harveast and IC — 1, Epicentr Agro — $ 0.42 million. Among these companies, Harveast and IC made the highest investments in innovative development per 1 hectare of agricultural land — 8.1 dollars, MHP — 6.9 $, Kernel and AP Group — 5 $, Astarta-Kyiv — 4 $ and Epicentr Agro — 3.8 $ per 1 hectare of agricultural land. However, despite these achievements, a mark of $ 50 / ha is considered acceptable. Due to the implementation of innovative measures Astarta-Kyiv saved about 15 million dollars in 4 years, Agroprosperis several times increased the efficiency of decisions made by agronomists, UkrLandFarming increased yields by a quarter. In general, according to experts, 80% of all spending on innovation is spent on computerization and automation of accounting processes, electronic document management, and protection of information from theft. Our study allowed us to analyze the work of company management in terms of areas of innovative development and to derive an indicator of integrated innovative development by segments and individual companies. This approach can be extrapolated to small and mediumsized agri-food enterprises. Анотація. Агропродовольча сфера була й залишається основою економіки України. На сьогодні, в умовах занепаду промисловості та всеохоплюваного процесу деіндустріалізації економіки, підприємства агропродовольчої сфери залишаються стабільно функціонуючими суб’єктами ринку. Попри перепони в розвитку, тривалий час на ринку агропродовольства домінують агрохолдинги, які акумулюють значні земельні масиви і фінансові ресурси. Найбільшими компаніями є Kernel, UkrLandFarming, MHP, Agroposperis та Astarta-Kyiv, земельні банки яких перевищують 200 тис. га. Зазначені компанії працевлаштували майже 75 тисяч працівників. Агрохолдинги інвестують у власний розвиток. Одним із пріоритетних напрямів є інноваційний розвиток. Саме інновації забезпечують стабільність і майбутнє компаніям. Найбільшим інноваційним фондом володіють Kernel, витрати якого становили 2,7 млн дол., MHP — 2,5, АP Group — 2, AstartaKyiv, Harveast та ІМС — 1, Epicentr Agro — 0,42 млн дол. З-поміж названих компаній на 1 га сільськогосподарських угідь найвищі інвестиції в інноваційний розвиток здійснили Harveast та ІМС — 8,1 дол., MHP — 6,9, Kernel та АP Group — 5, Astarta-Kyiv — 4 та Epicentr Agro — 3,8 дол. Однак, попри наведені досягнення, прийнятним вважається відмітка у 50 дол./га. За рахунок реалізації інноваційних заходів Astarta-Kyiv зекономила близько 15 млн дол. за чотири роки, Agroprosperis — зростання ефективності ухвалених рішень агрономами в декілька разів, UkrLandFarming — підвищити урожайність на чверть. У цілому ж, за даними фахівців, 80 % усіх витрат на інновації спрямовуються на комп’ютеризацію та автоматизацію облікових процесів, ведення електронного документообігу, забезпечення захисту інформації від крадіжок. Проведене нами дослідження дало змогу проаналізувати роботу менеджменту компаній у розрізі напрямів інноваційного розвитку і вивести показник комплексного інноваційного розвитку за сегментами та окремими компаніями. Цей підхід може бути екстрапольований на малі та середні підприємства агропродовольчої сфери.
Економічний розвиток підприємств агропродовольчої сфери на інноваційній основі
Keywords: innovation; інновації; economic development; економічний розвиток; agri-food enterprises; підприємства агропродовольчої сфери; business process management; управління бізнес-процесами; sustainable development; стійкий розвиток